Project-Based Learning with Recycled Bottle Planting: Effects on Young Childrens Cognitive and Gross Motor Skills - Lailil Murro; Rachma Hasibuan; Sri Setyowati (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Early childhood is a critical phase for developing both cognitive and gross motor abilities. However, many early education practices remain cognitively centered, providing limited structured motor stimulation. This study investigates the effect of Project-Based Learning (PjBL) through a recycled bottle planting project on the cognitive and gross motor development of children aged 5-6 years at RA Rachmat Bangil. Employing a quantitative approach with a quasi-experimental design, the study involved an experimental group participating in a series of hands-on activities designing, cutting, decorating bottles, planting seeds, and plant care while a control group received conventional instruction. Results showed that children in the PjBL group achieved significantly higher cognitive gain scores compared to the control group. Although improvements in gross motor skills were also observed, they were less substantial. The projects physical nature fostered coordination, balance, and movement in a meaningful and enjoyable context. These findings confirm that PjBL, even with simple materials, effectively supports holistic child development. The study suggests that early childhood educators integrate physical engagement within cognitive learning through contextual, environmentally conscious projects.